A mechanistic study of Toxoplasma gondii ROP18 inhibiting differentiation of C17.2 neural stem cells. Issue 1 (December 2017) - Zhang, Xian; Su, Rui; Cheng, Zhengyang; Zhu, Wanbo; Li, Yelin; Wang, Yongzhong; Du, Jian; Cai, Yihong; Luo, Qingli; Shen, Jilong; Yu, Li
Abstract Background Congenital infection ofToxoplasma gondii is an important factor causing birth defects. The neural stem cells (NSCs) are found to be one of the target cells for the parasite during development of the brain. As a key virulence factor of the parasite that hijacks host cellular functions, ROP18 has been demonstrated to mediate the inhibition of host innate and adaptive immune responses through specific binding different host immunity related molecules. However, its pathogenic actions in NSCs remain elusive. Results In the present study, ROP18 recombinant adenovirus (Ad-ROP18) was constructed and used to infect C17.2 NSCs. After 3d- or 5d–culture in differentiation medium, the differentiation of C17.2 NSCs and the activity of the Wnt/β-catenin signaling pathway were detected. The results showed that the protein level of βIII-tubulin, a marker of neurons, in the Ad-ROP18-transfected C17.2 NSCs was significantly decreased, indicating that the differentiation of C17.2 NSCs was inhibited by the ROP18. The β-catenin level in the Ad-ROP18-transfected C17.2 NSCs was found to be lower than that in the Ad group. Also, neurogenin1 (Ngn1) and neurogenin2 (Ngn2) were downregulated significantly (P < 0.05) in the Ad-ROP18-transfected C17.2 NSCs compared to the Ad group. Accordingly, the TOP flash/FOP flash dual-luciferase report system showed that the transfection of Ad-ROP18 decreased the Wnt/β-catenin pathway activity in the C17.2 NSCs. Conclusions The inhibition effect of the ROP18 fromT. gondii (TgROP18) on the neuronal differentiation of C17.2 NSCs was at least partly mediated through inhibiting the activity of the Wnt/β-catenin signaling pathway, eventually resulting in the downregulation of Ngn1 and Ngn2. The findings help to better understand potential mechanisms of brain pathology induced by TgROP18.